THE EFFECT OF DUOLINGO APPLICATION ON STUDENTS’ ENGLISH VOCABULARY MASTERY - Husnur Rosyidah Aulia; Eka Wahjuningsih; Rika Andayani (ELTR Journal, 2020)
This paper examined the effect of Duolingo application on students English vocabulary mastery using quasi-experimental with post-test only design. The participant of this research was the eighth-grade students in one of junior high school in Jember. In this study, the experimental group got treatment by using Duolingo application; meanwhile, the control group taught as usual by using flashcard as the media. The data was collected from vocabulary test and was analyzed by using SPSS with independent sample t-test. The result showed a significant difference between students who use Duolingo application and who didnt with the value of significance (0.017) which was less than 0.05 and the mean score of the experimental group (84.69) was higher than the mean score of the control group (80.78). This demonstrates that using Duolingo Application has a significant effect on students’ vocabulary mastery.